Using post‐incident behavioral analysis techniques to complement incident investigations. Issue 4 (26th September 2020) - McDonald, Jennifer
Abstract: The hours and days following an incident represent a very critical time to gather important information about the event. Post‐incident investigations are usually accompanied by root cause analyses to determine what led to the incident and to develop corrective actions to reduce the likelihood that the incident will occur again. Often, little thought may be given to the human factors aspect of the incident in terms of correcting the human behavior associated with the incident. As process safety professionals, we work to provide sound engineering solutions that usually involve replacing the human element with an automated system. In many situations, it may not be possible to completely eliminate the human factor component of the front‐line workers that resulted in the incident, but it may be possible to reduce the frequency of human error on future incidents by engaging the front‐line workers in post‐incident discussions that are rooted in behavior‐based safety. This paper describes the tools and techniques that we have developed to effectively facilitate post‐incident behavior‐based discussions. The target of these discussions is identifying how human error plays a key role in the incident and how behavior influences decision‐making during an incident.